Study of factors affecting arsenic release from sediment into groundwater - Khuê, Nguyễn Như; Trang, Phạm Thị Kim; Tươi, Hoàng Thị; Trang, Nguyễn Thị Thu; Mai, Nguyễn Thị Hoa; Trang, Cao Thị Mai; Lan, Vi Thị Mai; Việt, Phạm Hùng; Postma, Dieke (Vietnam Journal of Earth Sciences, 2013)
The arsenic (As) enrichment in groundwater of the river delta has been being studied and predicted. Organic matter degradation generating the reduced environment was a popular hypothetical mechanism which is convenient for Fe-oxides reductive dissolution leading to the As release. However, the role of each factor in this process has not fully understood. In this study, the relationship between the mineralogy and the concentration of As in the groundwater are discussed. Two research sites are chosen: the young river bank sediment site with sedimentary age less then 600 years and the old mountainside sedimentary age more then 3500 years one. The results of nanalysis showed that As concentration in the young sediment is 7,5 mg/kg which is double of it in the old sediment (3,9 mg/kg). The amount of the potentially removable As in the young sediment (2 mg/kg) is higher than that in the old sediment (0,34 mg/kg). The As associated with easily reducible Fe(III) and crystalline Fe was found in the young sediment totalled 4 mg/kg but it was not detected in the old sediment. Combined with the As concentration in the groundwater of two areas, the results showed that the more As bound on mobile Fe (easily dissolvable Fe-oxides, easily reducible Fe(III) phases and crystalline Fe phases) the higher possibility of the As enrichment in groundwater. The study suggests that the existence of As on Fe phases  could be flushed under reduced condition controls the As release from sediment into groundwater. Besides, the increasing of flushed Fe and As in the sediment incubated with river water added organic matter experiment was observed. This supports the hypothesis of organic matter role in As mobilization that is to genenrate the reduced condition enhancing the reductive dissolution of As bearing Fe-oxides which leads to the leaching of As.